TEACHING PRONUNCIATION OF FRICATIVE AND AFFRICATE SOUNDS THROUGH ENGLISH SONGS AT EIGHTH GRADE STUDENTS OF UPT SMP N 37 MEDAN - Talenta Br Tanggang; Rina Octavia Simarmata; Usman Sidabutar (Jurnal Scientia, 2023)
The aims of this research was to describe the students’ pronouncing fricative and affricate sounds through English songs. Many factors affect success or failure as a result of the teaching-learning process, especially in pronunciation. One of them is the environment or situation where and how is the teaching-learning process done. In many cases, the learning process is uninteresting because the technique used by the teacher, or the way the teacher delivers the materials is not attracting the students. This research was conducted at UPT SMP N 37 Medan. The population of this research was the XII grade students of academic year 2023/2024. There were 6 classes consisting of 180 students. The sample is divided into 1 class consisted of 30 students were taken by using random sampling technique. In completing the analysis, the researcher uses descriptive qualitative as the research method of the analysis. The instruments of collecting the data was a pronunciation test, recording, and transcribing. The results of this research showed that there are that the students excellent or good in pronouncing fricative sounds (14,7%) and almost correct or poor pronouncing affricate sounds (2,15%).